Complicated urachal cyst in two pediatric patients: a case report - Karol Kamel; Hadeer Nasr; Sherifa Tawfik; Ahmed Azzam; Mohamed Elsaid; Mohamed Qinawy; Ahmed Kamal; Heba Taher (BMC, 2023)
Abstract Background A urachal cyst has a rare incidence that has been reported as 1/5,000 live birth. Case presentation We report two patients with a complicated urachal cyst, a 5-year-old female who presented to the emergency department with severe abdominal pain and a 3-year-old female presenting with abdominal pain and constipation. Upon laparoscopic exploration both patients had complicated urachal cysts which were adherent to the urinary bladder. Conclusion Complicated urachal cysts can present with acute abdominal pain.